(untitled) (Historia, 2021)
The subtitle of the book “The untold story of the Desert War in World War II” already indicates that the author tried to add a new dimension to the history of the Desert War which in itself had been extensively researched by numerous historians. As recent as 2004 Niall Barr did ground breaking work with his book on the fighting near El Alamein in 1942 in Pendulum of War – The Three Battles of El Alamein, published by Jonathan Cape in London, exhibiting new discoveries from archival sources and visits to the battlefields. In 2012 the American University of Cairo took the initiative to arrange a symposium commemorating the 70th anniversary of the Desert War. The resultant papers submitted in Cairo found form in the book, El Alamein and the Struggle for North Africa. The whole spectrum of the war as experienced by different Commonwealth countries, the previous Axis forces and even an Egyptian perspective is included.